Distributed lock management for mobile transactions - Jin Jing; Bukhres, O.; Elmagarmid, A. (Proceedings of 15th International Conference on Distributed Computing Systems, 1995)
We present a new lock management scheme which allows a read unlock for an item to be executed at any copy site of that item; the site may be different from the copy site on which the read lock is set. The scheme utilizes the replicated copies of data items to reduce the message costs incurred by the mobility of the transaction host. We demonstrate this idea in an optimistic locking algorithm called O2PL-MT (Optimistic Two Phase Locking for Mobile Transactions). Like its counterpart algorithm O2PL (Optimistic Two Phase Locking), O2PL-MT grants read locks immediately on demand and defers write locks until the commitment time. However, O2PL-MT requires the transmission of fewer messages than O2PL in a mobile environment in which data items are replicated.